DOI: 10.33915/etd.6418
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Balanced Time Perspective in Adults across the Life Span

Abstract: The current study investigated balanced time perspective (BTP) in adults across the life span (N = 400, 43.3% males). Boniwell and Zimbardo (2004) defined BTP as the flow and flexibility of connecting to the past, living in the present, and looking forward to the future and argued that is an optimal time perspective associated with happiness and well-being. Using Time Attitude Scale (Mello & Worrell, 2012), younger (M = 26.09 years), middle-aged (M = 46.72 years), and older (M = 64.25 years) adults subjective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 61 publications
(237 reference statements)
0
5
1
Order By: Relevance
“…However, age was not significantly correlated with any of the other time perspectives: positive past (r = .11), positive present (r = .10), negative present (r = -.10), positive future (r = .00), and negative future (r = -.06). In the current study there is little to no relationship between age and future time perspective, these results may be contrary to Pichayayothin's (2014) results showing that older adults viewed their future as more negative and less positive.…”
Section: Time and Goalscontrasting
confidence: 99%
See 4 more Smart Citations
“…However, age was not significantly correlated with any of the other time perspectives: positive past (r = .11), positive present (r = .10), negative present (r = -.10), positive future (r = .00), and negative future (r = -.06). In the current study there is little to no relationship between age and future time perspective, these results may be contrary to Pichayayothin's (2014) results showing that older adults viewed their future as more negative and less positive.…”
Section: Time and Goalscontrasting
confidence: 99%
“…A multi-group analysis showed that the factor loadings of the TAS were invariant across the three age groups. Pichayayothin (2014) also found that all six subscales had a strong correlation with subjective well-being. Showing that the TAS may measure temporal well-being.…”
Section: The Nature Of Time Perspectivementioning
confidence: 72%
See 3 more Smart Citations